2017
DOI: 10.1007/s10549-017-4112-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic development of an abbreviated protocol for screening breast magnetic resonance imaging

Abstract: Rationale & objectivesWe sought to develop an abbreviated protocol (AP) for breast MRI that maximizes lesion detection by assessing each lesion not seen on mammography by each acquisition from a full diagnostic protocol (FDP).Materials & methods671 asymptomatic women (mean 55.7 years, range 40–80) with a negative mammogram were prospectively enrolled in this IRB approved study. All lesions on MRI not visualized on mammography were analyzed, reported, and suspicious lesions biopsied. In parallel, all FDP MRI ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 28 publications
2
28
0
2
Order By: Relevance
“…Also, in most of our subjects MRI was performed for the purpose of cancer staging. The respective mean and median tumor size were 3.8 cm and 2.8 cm for the entire study population and 1.4 cm and 1.49 cm for the smaller lesion subgroup, while in previous studies the reported sizes of mammographically occult cancers detected using MRI have been smaller, ∼1 cm . Further research is necessary to determine whether levels of agreement comparable to ours would be observed for tumors detected through a screening program.…”
Section: Discussionsupporting
confidence: 59%
“…Also, in most of our subjects MRI was performed for the purpose of cancer staging. The respective mean and median tumor size were 3.8 cm and 2.8 cm for the entire study population and 1.4 cm and 1.49 cm for the smaller lesion subgroup, while in previous studies the reported sizes of mammographically occult cancers detected using MRI have been smaller, ∼1 cm . Further research is necessary to determine whether levels of agreement comparable to ours would be observed for tumors detected through a screening program.…”
Section: Discussionsupporting
confidence: 59%
“…Given these different abbreviated MRI protocols, efforts have been made to identify the sequences that are necessary for a confident breast cancer diagnosis. Strahle et al used a full diagnostic protocol in 452 lesions to prospectively identify the most important sequences for breast MRI screening . They concluded that T 2 ‐weighted, T 1 ‐weighted precontrast, first and late postcontrast images are necessary and enable a rapid breast cancer screening with a scan time of 7.5 minutes.…”
Section: Abbreviated Mrimentioning
confidence: 99%
“…Multiple investigators are evaluating if these rapid MRI exams are cost‐effective enough to provide the initial diagnosis . In breast imaging, one of the goals is to evaluate if an abbreviated breast MRI may be a first‐line exam and compete with other imaging exams such as 2D screening mammograms, digital breast tomosynthesis, and whole breast screening ultrasound exam.…”
Section: Abbreviated Mri As a Valuable Initiativementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Grimm et al investigated the addition of a second postcontrast image to an abbreviated protocol and did not detect a significant difference in diagnostic accuracy . In accordance, Strahle et al found the same intensities of lesion depiction on their first and second subtraction images . Romeo et al used an abbreviated protocol with subtraction series from three different timepoints but did not evaluate the additional benefit of the later timepoints compared with the FAST protocol…”
Section: Emerging Techniques and Outlookmentioning
confidence: 99%